2016
DOI: 10.4103/1319-3767.195552
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyschizandrin suppresses dss-induced ulcerative colitis in mice

Abstract: Background/Aims:Deoxyschizandrin as one of the most important component of Schisandra chinensis (Turcz.) Baill plays an immunomodulatory role in a variety of diseases, yet its role in ulcerative colitis remains to be elucidated. We aimed to investigate the role of deoxyschizandrin in DSS-induced ulcerative colitis in mice.Patients and Methods:In the present study, an inflammation model of cells was constructed to confirm the anti-inflammatory effect of deoxyschizandrin. Then a mouse model with Dextran sulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The present study explored the effects of YMJ on DSS-induced mouse models of UC. The DSS-induced UC mouse model is a common experimental method used to investigate intestinal inflammation ( 31 ). Previous studies have shown that YMJ can improve mucosal injury, and can reduce the extent and severity of injury ( 22 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study explored the effects of YMJ on DSS-induced mouse models of UC. The DSS-induced UC mouse model is a common experimental method used to investigate intestinal inflammation ( 31 ). Previous studies have shown that YMJ can improve mucosal injury, and can reduce the extent and severity of injury ( 22 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mice were randomly divided into 7 groups, 10 in each group: control group (CON group), UC model group (UC group), sulfasalazine positive control group (SASP group), chlorogenic acid low dose group (CGA-L group), chlorogenic acid middle dose group (CGA-M group), chlorogenic acid high dose group (CGA-H group), and ERK inhibitor plus chlorogenic acid treatment group (E+CGA group). In addition to the CON group, the ulcerative colitis model was made as described in the literature [25]. The dextran sodium sulfate (DSS) was dissolved in distilled water to prepare a 5% DSS solution, and the mice were allowed to freely drink the solution for 7 days, and then to drink distilled water for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…BDNF possesses significant effects on differentiation, growth, and damage restoring and could maintain the normal function of sensory nerve [16, 17]. The increased level of BDNF may result in various abnormal feelings related to pains such as chronic pain, inflammatory pain, visceral pain, and high sensitivity [18].…”
Section: Introductionmentioning
confidence: 99%